Kombinasi Pijat Marmet dan Kompres Hangat terhadap Pengeluaran Asi pada Ibu Nifas (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effectiveness of a combination of marmet massage and warm compresses on breast milk production in postpartum mothers. The method used is quantitative research with a quasi-experimental research design. The study's results showed a difference in the effectiveness of the combination of marmet massage and warm compress on breast milk production in postpartum mothers with a p-value of (0.032